2016
DOI: 10.1177/0040517516629143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on standard and new test methods for evaluating the effects of structural firefighting gloves on hand dexterity

Abstract: This research identifies laboratory test methods designed to advance assessment of the effects of structural firefighter gloves on a firefighter's ability to perform tasks with their hands. Two new hand dexterity test methods are discussed: a modified tool test for measuring glove effects on gross or whole hand motor control, and a novel cylinder lift method for evaluating glove effects on fine or fingertip hand dexterity. Data generated by testing a representative group of structural firefighter and other res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…As a result, MTDT has been recommended to be used for accomplishing this purpose [ 26 , 40 ]. The results of the present study revealed that MTDT had a lower discrimination power than HTDT which is in contradiction with the results of the study carried out by Barker et al [ 31 ]. This contradiction can be attributed to the low sample size of Barker's study or the different types of gloves investigated in these two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As a result, MTDT has been recommended to be used for accomplishing this purpose [ 26 , 40 ]. The results of the present study revealed that MTDT had a lower discrimination power than HTDT which is in contradiction with the results of the study carried out by Barker et al [ 31 ]. This contradiction can be attributed to the low sample size of Barker's study or the different types of gloves investigated in these two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…MTDT has been developed to assess the dexterity of hands and fingers while wearing firefighting gloves. National Fire Protection Association (NFPA) recommends to use this test instead of Bennet dexterity test [ 30 , 31 ]. It is composed of a set of bolts, nuts, washers, and a vertical board as demonstrated ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric data are the basis of the ergonomic design used in size systems and are therefore used extensively in the development of products and equipment such as clothes, helmets and other wearable products, as well as for furniture and work equipment (Cakit et al, 2014;Carneiro et al, 2017;García-Cáceres et al, 2012;Liu et al, 2018Liu et al, , 2016Mououdi et al, 2018;Pang et al, 2018;Park and Langseth-Schmidt, 2016;Skals et al, 2016;Verwulgen et al, 2018;Zheng et al, 2007). Products that fit subjects' anthropometric dimensions better are more comfortable and lead to enhanced performance (Barker et al, 2017;Carneiro et al, 2017;García-Cáceres et al, 2012;Pang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the studied textile materials were evaluated using a grip strength test (Figure 1), which provided indirect information about their anti-slip properties. Those properties are of great relevance to user comfort and ergonomics, as they significantly affect grip strength [1,10,36]. The highest grip strength was exhibited by the knitted aramid fabric D-1, woven glass fiber fabric T-1, silicone-coated knitted aramid fabric DP-3, and dotcoated knitted aramid fabric DN-1.…”
Section: Discussionmentioning
confidence: 99%